Un recuerdo de la infancia. Juego, experiencia y memoria en los escritos de Walter Benjamin - Peller, Mariela (Nómadas. Critical Journal of Social and Juridical Science, 2010)
One of the objectives of the work of Walter Benjamin was to generate a different notion of experience, which involved giving it a potential for redemption. It was in the children's ability to see colors in isolation of it forms, where he placed, first, that utopian and redemptive notion of experience. From this link between childhood, memory and experience, this essay explores the figures and practices, which according to Benjamin embody the possibility to generate experience in a world where it would be extinct. This article concludes that, like the figures studied in his texts (the narrator, the copyist, the collector, the child, the bricoleur and the poet), Benjamin did with his working method attempts to revive the experience.
Keywords: Walter Benjamin; Memory; Game; Experience; Childhood